Microscopic Study on the Diameter of the Pineal Calcification of Bangladeshi Cadavers (Bangladesh Journal of Anatomy, 2013)
Context: The human pineal gland is characterized by the presence of calcified concretions, called pineal acervuli or brain sand. These are basophilic extracellular bodies. The study was carried out to describe the microscopic features of pineal calcifications and to find out age related changes. Study Design: Cross sectional descriptive type of study. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka, from July 2009 to June 2010. Materials: 60 postmortem human pineal glands were collected from unclaimed dead bodies that were under examination in the morgue of Department of Forensic Medicine, Dhaka Medical College, Dhaka. Methods: The samples were divided into four different age groups, i.e. Group-A (15-30 years), Group-B (31-40 years), Group-C (41-50 years) and Group-D (>50 years). Histological study was carried out on relatively 27 fresh samples. Results: The mean diameter of the pineal calcifications were 351.14±111.69 ?m in group A, 600.00±232.69 ?m in group B, 909.43±124.18 ?m in group C and 1541.67±224.54 ?m in group D. The differences in diameter of the pineal calcifications between group A & C, A & D, B & C, B & D and C & D were statistically significant. Conclusion: Age related changes were found in the diameter of pineal calcifications. DOI: http://dx.doi.org/10.3329/bja.v9i2.15220 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.71-74